Two Perspectives on the Same Source: An Examination of Federal Deportation Case Files - Scheinberg, Ellen (Archivaria, 2004)
This article investigates the appraisal and use of deportation case files from the perspective of an archivist as well as an historian. The author outlines her experiences in both capacities – as an archivist with the Library and Archives Canada and later on as a Ph.D. student in history – in order to demonstrate how her perception of this source changed dramatically after she switched from one role to the other. In addition to outlining the re-appraisal work she undertook with these records at the NAC as well as the research involved in her dissertation, the article suggests some possible solutions as to how the different priorities and needs associated with these two groups might be resolved in the future, without threatening the independence required by archivists when undertaking appraisal and re-appraisal initiatives. RÉSUMÉ Cet article examine l’évaluation et l’utilisation des dossiers individuels de déportation, du point de vue de l’archiviste aussi bien que de l’historien. L’auteure expose les grandes lignes de ses deux expériences, comme archiviste à la Bibliothèque et Archives Canada et plus tard comme étudiante de doctorat en histoire, afin de montrer comment sa perception de la source a changé énormément en passant d’un rôle à l’autre. En plus de décrire le travail de ré-évaluation de ces dossiers qu’elle a fait aux BAC, de même que la recherche entreprise au cours de son doctorat, l’auteure suggère quelques solutions pour résoudre les problèmes posés par les priorités et les besoins différents des archivistes et des chercheurs, sans pour autant menacer l’indépendance requise par les archivistes pour mener à bien leur travail d’évaluation et de ré-évaluation.